The influence of organizational justice and demographic variables on employee willingness to engage in customer oriented behaviour / Sarminah Samad and Zaini Abdullah - Samad, Sarminah; Abdullah, Zaini (Universiti Teknologi MARA Cawangan Pahang, 2007)
The purpose of this study was to examine the relationship between organizational justice and demographic variables with employee willingness to engage in customer oriented behavior. Consequently, the study was to determine the influence of demographic variables and organizational justice on employee willingness to engage in customer oriented behavior. Regression analysis on a sample of 292 respondents derived from the selected cellular retail centers in Klang Valley indicated that all organizational justice dimensions and demographic variables were found to have significant relationships with employee willingness to engage in customer oriented behavior. The study also revealed that organizational justice dimensions and demographic variables had a positive effect on customer oriented behavior. It was found that procedural justice had more significant effect on customer oriented behavior than distributive justice and emerged as the most significant predictor on employee willingness to engage in customer oriented behavior. Implications of the findings and suggestions for future research are discussed.